Low defects, large area and high stability of all-inorganic lead halide perovskite CsPbBr3 thin films with micron-grains via heat-spraying process for self-driven photodetector. Issue 51 (15th August 2018) - Zhou, Huawei; Fan, Lin; He, Guohang; Yuan, Cang; Wang, Yunying; Shi, Shaozhen; Sui, Ning; Chen, Baoli; Zhang, Yingtian; Yao, Qingxia; Zhao, Jinsheng; Zhang, Xianxi; et al.
Abstract : In this study, large area, low defect and high stable all-inorganic lead halide perovskite CsPbBr3 thin film with micron-grains (MG-CsPbBr3 -TF) are prepared via heat-spraying process (HSP) using CsPbBr3 saturated solution (CsPbBr3 -SS). Abstract : All-inorganic lead halide perovskite CsPbBr3 has important applications in photoelectronic devices such as photodetectors, LEDs and photovoltaic devices. However, preparing high-quality CsPbBr3 thin films has proven to be challenging. In this study, we prepared all-inorganic lead halide perovskite CsPbBr3 thin films with micron-grains (MG-CsPbBr3 -TF) via a heat-spraying process (HSP) using a CsPbBr3 -saturated solution (CsPbBr3 -SS), and the films exhibited large area, low defects and high stability. The grain size of MG-CsPbBr3 -TF was about 1–5 microns. The micron-sized grains in MG-CsPbBr3 -TF enabled the absorption cutoff edge to be extended from 537 to 545 nm. In addition, the presence of fewer boundaries in MG-CsPbBr3 -TF reduced the defects in MG-CsPbBr3 -TF (the blue shift of luminescence). The response wavelengths of a low-cost and self-driven (zero-biased) photodetector based on MG-CsPbBr3 -TF were from 330 to 600 nm. CsPbBr3 thin films having a large area (10 cm × 10 cm) and micron-sized grains were also prepared by HSP and exhibited excellent stability (1944 h) in air ( T = 298 K, 40% humidity). To the best of our knowledge, this is the first study of high-quality CsPbBr3 thin films prepared by HSP. The results are of great interest for both fundamental research and practical applications of CsPbBr3 in photodetectors, LEDs and photovoltaic devices.